Exploring the islamic world with technology: integrating technology in the islamic education curriculum - Syarifah, Hasnia Imroatis; Romadhoni, Muhammad Fadhil; Taufiq, Mahdy Haidar (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
The advancement of technology is continuously improving. Technology has been employed by several entities to streamline their operations, including the realm of education. Technology-based curriculum involves integrating hardware and software products into the curriculum to enhance the learning process for students and improve the effectiveness and enjoyment of education. Given that the curriculum is the primary element of education, its advancement in tandem with technology should facilitate the attainment of curriculum objectives, encompassing learning outcomes, instructional approaches, and the provision of educational resources and evaluations. The purpose of this study was to investigate the integration of technology into the curriculum of Islamic Religious Education. Regarding the methodology, the author employed the research library using a qualitative approach, which included a description and analysis of the research findings, as well as other supporting literature from books and scientific journals as writing components. The findings emphasise the importance of integrating technologies into the Islamic Religious Education curriculum, taking into account its relevance and effectiveness in the digital age. Due to its numerous benefits such as increased student involvement and improved accessibility, educational technology holds great potential for enhancing the quality of instruction in Islamic Religious Education.